Sustainable foamed Poly-Al composites from used beverage cartons using azodicarbonamide - Anin Memon; Suchalinee Mathurosemontri; Wichain Chailad; Waroonsiri Jakrabutr; Nichanan Phansroy; Kullawadee Sungsanit; Porakoch Sirisuwan; Ponlapath Tipboonsri (Results in Engineering)
This study presents a direct method for fabricating chemically foamed composites from used beverage cartons (UBCs), utilizing recycled polyethylene–aluminum (Poly-Al) waste and azodicarbonamide (ADC) as a chemical blowing agent. The influence of ADC concentration (0.5–2.0 phr) on foam morphology, density, and mechanical properties was systematically investigated. At 1.0 phr ADC, the foam exhibited the lowest density (0.37 g/cm³, a 55% reduction from the unfoamed Poly-Al), the highest volume expansion ratio (2.21), the maximum cell density (3.28 × 10³ cells/cm³), and a balanced average cell size (582.69 µm). The mechanical properties showed a trade-off with weight reduction: the 1.0 phr ADC sample retained approximately 14% of the original Young’s modulus (697.2 MPa) and 23% of the tensile strength (1.03 MPa), suggesting an optimal balance for lightweight applications. Excessive ADC loading (1.5–2.0 phr) led to over-foaming, increased cell size (up to 647.33 µm), reduced cell density, and mechanical degradation, confirming the importance of controlling gas evolution relative to matrix melt strength. The incorporation of embedded aluminum particles further contributed to dimensional stability by reinforcing the matrix, as observed in SEM analysis. This work highlights a scalable approach to upcycling multilayer UBC waste into lightweight, functional composite foams, offering insights into gas–melt interactions and promoting sustainable material development.